2017
DOI: 10.1080/01616412.2017.1315864
|View full text |Cite
|
Sign up to set email alerts
|

A review of sleep disorders and melatonin

Abstract: Sleep disorders are a group of conditions that affect the ability to sleep well on a regular basis and cause significant impairments in social and occupational functions. Although currently approved medications are efficacious, they are far from satisfactory. Benzodiazepines, antidepressants, antihistamines and anxiolytics have the potential for dependence and addiction. Moreover, some of these medications can gradually impair cognition. Melatonin (N-acetyl-5-methoxytryptamine) is an endogenous hormone produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
181
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(221 citation statements)
references
References 58 publications
2
181
1
11
Order By: Relevance
“…Melatonin is a hormone produced by the pineal gland during nocturnal periods to control the circadian sleep–wake rhythms by enhancing sleepiness (reviewed in Ref. ). There is evidence that insomnia described in AS children is caused by low levels of melatonin.…”
Section: Therapeutic Strategies In Clinical Trialsmentioning
confidence: 99%
“…Melatonin is a hormone produced by the pineal gland during nocturnal periods to control the circadian sleep–wake rhythms by enhancing sleepiness (reviewed in Ref. ). There is evidence that insomnia described in AS children is caused by low levels of melatonin.…”
Section: Therapeutic Strategies In Clinical Trialsmentioning
confidence: 99%
“…It is well known that melatonin hormone is one of the key regulators of circadian biorhythms and violation of its secretion in menopausal women might lead to changes in metabolism and the formation of various diseases, including sleep disturbances. Studies carried out to date have been shown that people with insomnia have a lower melatonin level [55]; moreover, the peak of the hormone secretion is shifted, which have been demonstrated in the study on the association of melatonin, menopausal depression and sleep time. A delay in the peak of hormone secretion before morning have been revealed in women with menopausal depression, which, according to researchers, may be caused by longer sleep duration as a compensation for insomnia in these women [56].…”
Section: Discussionmentioning
confidence: 82%
“…В настоящее время показано, что какие-либо изменения в работе циркадной системы повышают риск развития таких патологических состояний, как нарушения сна [46], аффективные расстройства [28], диабет [36], онкология [22], пре-эклампсия [16], ожирение [33], сердечно-сосудистые заболевания [39], репродуктивные нарушения [48].…”
Section: Abstract: Circadian Rhythms Melatonin Menopause Sleep DIunclassified
“…Проведёнными к настоящему времени исследова-ниями показано, что люди, страдающие инсомниче-скими расстройствами, имеют более низкий уровень мелатонина [23,26,35,46]. Более того, при инсомнии не только меняется уровень мелатонина, но и смеща-ется пик секреции данного гормона, что было про-демонстрировано в работе по изучению ассоциации мелатонина, менопаузальной депрессии и времени сна.…”
Section: Abstract: Circadian Rhythms Melatonin Menopause Sleep DIunclassified